2008
DOI: 10.1063/1.2899936
|View full text |Cite
|
Sign up to set email alerts
|

Neutron reflectometry study of hydrogen desorption in destabilized MgAl alloy thin films

Abstract: We studied the hydrogen absorption and desorption properties of thin Pd-covered Mg1−xAlx alloy films as a function of temperature and alloy composition. Using neutron reflectometry, we were able to determine the hydrogen content and the hydrogen distribution within these MgAl films in situ. For all films, hydrogen was uniformly dispersed within the MgAl film and no hydrogen was observable in the Pd cover layer. The Mg0.7Al0.3 film shows an appreciable 4.1wt% stored hydrogen and improved desorption characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30] This ability is empowered by the high contrast between hydrogen isotopes (hydrogen and deuterium) which can be used to precisely probe, non-destructively, the amount of hydrogen penetrating into the metal and any surface films. The fact that NR can be carried out in situ by applying a controlled electrochemical condition adds a new dimension to the study of hydrogen transport through the oxide and metal films, and of their corrosion resistance.…”
Section: 8-13mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] This ability is empowered by the high contrast between hydrogen isotopes (hydrogen and deuterium) which can be used to precisely probe, non-destructively, the amount of hydrogen penetrating into the metal and any surface films. The fact that NR can be carried out in situ by applying a controlled electrochemical condition adds a new dimension to the study of hydrogen transport through the oxide and metal films, and of their corrosion resistance.…”
Section: 8-13mentioning
confidence: 99%
“…Later, Munter et al showed how deuterium absorption could be monitored in-situ during loading experiments on thin Pd films 9,10 . More recently, a series of studies has been published by Fritzche et al, showing how NR can be used to investigate the thermodynamics of hydrogen uptake process in Pd-capped metal alloy films [11][12][13][14][15] . NR has also proved an efficient way to characterize deviations in the hydrogen stoichiometry in very thin interface layers 9,16 , and can be used to determine inter-diffusion of elements at the interfaces of metal hydride films 11,12 .…”
mentioning
confidence: 99%
“…D has a positive coherent scattering length for neutrons, and thereby contributes to an increase in the SLD as opposed to H. If two sets of samples are prepared in the same way but one with H the other with D, the difference in SLD can give an accurate estimation of the H/D content of the sample. Similarly, NR has been used to study loading/unloading of H in metallic films, where the SLD prior to and post-loading is compared in order to estimate the H concentration 9,11,13,15,20,21 .…”
mentioning
confidence: 99%
“…Absorption and desorption properties of Pd-covered MgyAl1-y alloy thin films was studied as a function of temperature and alloy composition by means of neutron reflectivity technique (NR) [105]. Hydrogen absorption was performed at 430K for 20h at 6.8 MPa.…”
Section: Binary and Ternary Mg-based Alloysmentioning
confidence: 99%